PERAN KUALITAS PELAYANAN DAN KEPERCAYAAN MEREK DALAM MEMBANGUN LOYALITAS MEREK (STUDI KASUS PADA PT. TIKI JALUR NUGRAHA EKAKURIR) - Chelsi Felisia; Tumpal J.R Sitinjak (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
With all the improvement of technologies, Many industries use the advantages of this eras conveniences, one of those industries is online businesses. One of the influenced industries from this online business is delivery services or courier because when ordering online, automatically sellers will use delivery services to deliver their customers orders, especially intercity or island. One of the most famous delivery service company is JNE. This study use theory that will support the study with the definition and dimensions of service quality, brand trust, and brand loyalty. The object of this study is the delivery service company PT. Tiki Jalur Nugraha Ekakurir (JNE). To collect the data, this study uses a questionnaire to 100 respondents. This study uses descriptive analysis and Double linear regression analysis with SPSS 20 software. This study shows that service quality has been proven effected brand loyalty, and brand trust is also have been proven effected brand loyalty. This study concludes that service quality and brand trust have been proven effected brand loyalty. Keywords: Service Quality, Brand Trust, Brand Loyalty